Age estimation in three distinct east Asian population groups using southern Han Chinese dental reference dataset - Jayakumar Jayaraman; Hai Ming Wong; Graham J. Roberts; Nigel M. King; Hugo F. V. Cardoso; Pavethynath Velusamy; Ronaldo G. Vergara; Keni-ichi Yanagita; Teekayu P. Jorns (BMC, 2019)
Abstract Background Dental age estimation can assist in the identification of victims following natural disasters and it can also help to solve birth date disputes in individuals involved in criminal activities. A reference dataset (RDS) has been developed from the dental development of 2306 subjects of southern Han Chinese origin and subsequently validated. This study aimed to test the applicability of the southern Han Chinese dental maturation RDS on three distinct East Asian population groups. Methods A total of 953 dental panoramic radiographs of subjects aged 2 to 24 years were obtained from Philippines, Thailand and Japan. The staging of dental development was conducted according to Anglo-Canadian classification system. The dental age (DA) was calculated using six methods; one un-weighted average and five weighted average (n-tds, sd-tds, se-tds, 1/sd-tds, 1/se-tds) methods based on the scores of the southern Han Chinese RDS. Statistical significance was set at p < 0.05 and the variation between chronological age (CA) and DA was evaluated using paired t-test and Bland & Altman scatter plots. Results From six dental age calculations, all methods of DA accurately estimated the age of Japanese and few methods in Filipino subjects (n-tds, 1/sd-tds, 1/se-tds). There was consistent overestimation of age for all the methods for Thai females (p < 0.05). Conclusions The southern Han Chinese dental reference dataset was shown to be most accurate for Japanese, followed by Thai males and it was particularly ineffective for Filipinos and Thai females.